Kandungan Gizi Donat dengan Penambahan Ubi Ungu (Ipomoea Batatas L.) Sebagai Makanan Jajanan Berbasis Pangan Lokal Bagi Anak Sekolah - Riva Mustika Anugrah; Ela Suryani (Universitas Muhammadiyah Semarang, 2020)
Doughnut as one of popular snack by school children. Doughnut development isneeded to improve nutritional quality and physical characteristics. Purple sweet potato as a local food with attractive calour, sweet taste and high anthocyanin can be processed for addition ingredients of doughnut. The purpose of this research was to determine contained of nutrient and acceptance of purple sweet potato doughnut as snack based on local food for school children. This experiment investigated formulation of purple sweet potato doughnut with the ratio of purple sweet potato: wheat flour 20:80 ( F1), and 30:70 (F2). Analyzed of protein nutrients with micro kjehdal, fat with soxhlet and carbohydrates with anthron. Statistical analysis of acceptance used Mann-Whitney test. The result in this study was analyzed of the nutritional value of F1 sweet purple potato doughnut very serving (40g) containing energy: 158.46 kcal, Protein: 5 g, Fat: 9.92 g, Carbohydrates: 12.34 g and F2 energy: 169.51 kcal, Protein: 7.5 g, Fat: 11.32 g, Carbohydrates: 9.4 g. The acceptance test was performed no differences in color, texture, taste and aroma in the two purple sweet potato donuts formulas (p≥0.05). The energy content of F2 can contributed 10.27% energy need of school children.Keyword : children school, doughnut, local food, sweet purple potato